How to do research a practical guide to designing and managing research projects - Moore, Nick (Facet Publ., 2006)
Nick Moore provides practical help and guidance to anyone undertaking research, evaluating services, students undertaking projects and those involved in research method course design in the social sciences.
Keywords: Onderzoek; Recherche - Méthodologie; Research -- Methodology; Forschungsmethode; Projektmanagement; Forschungsprojekt